Investigação da auto e heteropercepção de comportamentos autênticos nas lideranças de uma instituição financeira cooperativa - Arcari, Ângela Duque (Universidade do Vale do Rio dos Sinos, 2025)
This study examined leaders’ self-perceptions and followers’ other-perceptions of Authentic Leadership (AL)behaviors in a Brazilian cooperative financial institution, a topic of growing relevance given the expansion and socioeconomic impact of cooperativism in the country. A mixed-methods design was adopted: a quantitative phase applying the Authentic Leadership Questionnaire (ALQ) with a sample of 162 participants (57 leaders; 105 followers) across different levels of the leadership pipeline, and a qualitative phase with individual interviews of four senior executives. Results indicated no significant difference in the ALQ total score between leaders and followers (Mann–Whitney U test, p = 0.406), with similar medians (leaders = 3.06; followers = 3.00). In multivariate analysis, education level predicted the overall ALQ score, suggesting more critical assessments of authenticity among more highly educated respondents; sex did not remain a significant predictor in the final model. In the qualitative phase, facilitators (coherence between discourse and practice; inspiration and ethical consistency) and barriers (limited time for high-quality conversations; politicized contexts; need for psychological safety) emerged. Integrating these findings supports the adequacy of the ALQ for the studied context and informs a development roadmap combining diagnosis (ALQ), guided debriefing, and management artifacts (forums for voice, information openness, decision rituals, and explicit justification of decisions). In sum, the study recommends strengthening participation structures, voice, and transparency, and instituting periodic monitoring via the ALQ to sustain authenticity in everyday routines and its effects on people and organizational decision-making.
Keywords: Liderança autêntica; Authentic leadership questionnaire (ALQ); Desenvolvimento de liderança; Capacidades psicológicas; Cooperativas; Authentic leadership; Leadership development; Psychological capacities; Cooperatives; ACCNPQ::Ciências Sociais Aplicadas::Administração